EKONOMI ISLAM DALAM MEWUJUDKAN FOOD ESTATE - Astuti, Meti (At-Tauzi : Jurnal Ekonomi Islam, 2023)
The role of Food Estate in a country's political economy is crucial, as hunger can lead to severe social, economic, and political crises. This paper analyzes Indonesia's loss of food sovereignty, particularly during the cooking oil scarcity, and explores Islamic Economics' solutions. Firstly, Islamic Economics aims to eradicate market distortions like hoarding and prevent cartels from controlling the supply chain. Secondly, maintaining supply-demand balance involves state oversight of cooking oil production, distribution, and rational consumption promotion. Using a descriptive qualitative approach and Islamic references, the study concludes that cartels caused cooking oil scarcity in Indonesia, weakening state control. Implementing Islamic economic strategies can reclaim state control and safeguard food sovereignty.